Interpreting Nrimo Ing Pandum Values in Bullying Survivors: Implications for Psychoeducational Services in Schools - Achmad Miftachul 'Ilmi; Vira Mulyawati; Nur Lailatul Khoiriyah (Journal of Cultural Guidance and Counseling, 2026)
Bullying in school settings is a serious issue that significantly affects adolescents’ psychological well-being and identity formation processes. Recovery from bullying is determined not only by the traumatic experiences encountered but also by how adolescents interpret and construct meaning from these experiences within their social and cultural contexts. This study aimed to explore the subjective experiences of adolescent bullying survivors, identify the role of the cultural value of Nrimo Ing Pandum in the self-recovery process, and formulate its implications for psychoeducational services in schools. This study employed a qualitative approach with a phenomenological design. The participants consisted of three adolescent bullying survivors as key informants and two school counselors as supporting informants. Data were collected through in-depth interviews and observations and were analyzed using the interactive analysis model of Miles and Huberman. The findings revealed that the experiences of bullying survivors were characterized by complex, fluctuating, and non-linear emotional dynamics. The value of Nrimo Ing Pandum functioned as a culturally grounded meaning-making framework that helped adolescents manage negative emotions, facilitate adaptive self-adjustment, and achieve reflective self-acceptance. The integration of this cultural value into psychoeducational services has the potential not only to support individual recovery but also to strengthen a more empathetic and supportive psychosocial school climate. This study recommends the development of psychoeducational services grounded in the value of Nrimo Ing Pandum through contextualized media as a preventive effort against bullying and encourages further studies to empirically examine the effectiveness of culturally based interventions.